Gambaran Postur Kerja Dengan Keluhan Musculosceletal Disorders (Msds) Pada Pekerja Borongan Pernis di PT. Spindo Tbk, Unit II - Putri Ekawati Ariyantono; Friska Ayu; Merry Sunaryo; Moch Sahri (Peneliti.net, 2022)
Poor work posture and a low level of work skills can result in injury to the work hazard of Musculosceletal Disorders (MSDs). Work postures that are not ergonomic are at risk for experiencing complaints of Musculosceletal Disorders (MSDs). One of the workers who are at risk for experiencing Musculosceletal Disorders complaints are workers who still carry out manual lifting and transporting jobs, such as the wholesale varnish workers at PT. SPINDO Tbk, Unit II. The purpose of this study was to describe work postures with complaints of Musculosceletal Disorders in lacquer wholesale workers at PT. SPINDO Tbk, Unit II. This research method is quantitative descriptive with a cross sectional study approach. The number of samples is the same as the population, which is 9 people taken using the total population. Data collection consists of primary data such as the number of workers, age, length of service, years of service, education level obtained from the company. Primary data such as work posture using the REBA assessment sheet while complaints of Musculosceletal Disorders using the Nordic Body Map assessment sheet. The results of this study indicate that most of the lacquer wholesalers work with a working posture with a moderate risk category of 66.6%, so that the complaints of Musculosceletal Disorders felt by workers in the slightly sick category are 28.5% of the right upper arm. Therefore, it is recommended for companies to provide education to workers regarding ergonomic risk control techniques in terms of work attitudes to reduce complaints of Musculosceletal Disorders while workers should stretch before starting work.